Budget Implementation as a Work Control Tool Work at the Mulyorejo Pratama Tax Service Office - Santoso, Joys Oktavia; Riyadi, Slamet (LPPPIPublishing, 2024)
This research has a topic of application regarding the operational budget by analyzing the operational budget and knowing how the budget as an instrument of control. The method in this study was an interview with sources at the Mulyorejo Tax Service Office in Surabaya. Processing of operational budget data using budget variance analysis. The results obtained are that the budget is so that all employees can carry out activities or activities in accordance with the work program that has been set. The results of the variance analysis of the operational budget with its realization are using favorable (profitable). These results show that the office has made rare efficiency in terms of operations.